Exhausting the inexhaustible: reading the structure of Samuel Beckett's Come and Go through Ashish Avikunthak's Endnote. Issue 2 (23rd February 2017) - Chattopadhyay, Arka
ABSTRACT: When Ashish Avikunthak, the experimental Indian film director adapts Samuel Beckett's 1965 'dramaticule' Come and Go into his 2005 Hindi short film Antaral or Endnote, he unsettles the mathematically precise structure of Beckett's play. Avikunthak plays around with the order of entries and exits of the three women who participate in the haunting transmission of an inaudible secret in Beckett's play. And his playful rearrangements underline the fundamental question about the number of secrets travelling among the women. Is it one or more than one secrets they share? The article answers this question through a thorough reading of the play's structure concentrating on differences between the play and the film in a comparative analysis of the original and its decisively deconstructive adaptation. The article seeks to illuminate the inter-penetration of form and content in Beckett's work and see how Avikunthak's manifold modifications are uncannily haunted by the principle of the Beckettian structure. The comparative study unravels the precise logic of Beckett's structure, its explicit and implicit rules and the rationale behind its precise points of commencement and termination.